2006
DOI: 10.1183/09031936.06.00032906
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bronchial CD4+ T-cell density in smokers with occupational asthma

Abstract: Cigarette smoking may alter bronchial inflammation in asthma. Multicolour immunohistofluorescent examination on bronchial cryosections was used to examine bronchial inflammatory cell infiltrate in patients with occupational asthma. Monoclonal antibodies to CD3, CD4, CD8, T-cell receptor-d1, CD68 and human leukocyte antigen-DR were combined to identify Tcell subsets and macrophages in bronchial biopsies from 20 workers with occupational asthma (12 smokers and eight nonsmokers), 15 healthy workers (seven smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
4
7
1
Order By: Relevance
“…The investigations by Fournier et al [32], Ricciardolo et al [34] and Tavora et al [36] focused only on bronchial IELs and did not examine IELs versus LPLs. Reports by Power et al [33] and Sjaheim et al [35] compared phenotypes of IELs and LPLs in control subjects and showed that the CD4/CD8 ratio is lower in IELs than LPLs, similar to our observations. However, the CD4/CD8 ratios reported by both of these authors were lower than what we observed in control subjects.…”
Section: Discussionsupporting
confidence: 82%
“…The investigations by Fournier et al [32], Ricciardolo et al [34] and Tavora et al [36] focused only on bronchial IELs and did not examine IELs versus LPLs. Reports by Power et al [33] and Sjaheim et al [35] compared phenotypes of IELs and LPLs in control subjects and showed that the CD4/CD8 ratio is lower in IELs than LPLs, similar to our observations. However, the CD4/CD8 ratios reported by both of these authors were lower than what we observed in control subjects.…”
Section: Discussionsupporting
confidence: 82%
“…A reduction in CD4 + lymphocytes, as observed by us, has been reported when comparing smoking and nonsmoking mild asthma with occupational asthma [29]. We also saw an increase in absolute numbers of neutrophils in the blood and a decrease in FeNO in the SAs/ex group compared with the SAn group.…”
Section: Discussionsupporting
confidence: 68%
“…These effects are also reported in milder asthma [30][31][32]. Other inflammatory changes observed in response to smoking in milder asthma include a reduction in blood [30] and sputum eosinophils [30,33], increases in sputum neutrophils [29], and increased submucosal CD8 + lymphocytes and macrophages in bronchial biopsies [34]; however, we did not see these differences in our severe asthma subjects.…”
Section: Discussioncontrasting
confidence: 49%
“…It is possible that the higher number of both CD4 and CD8 cells in the peripheral blood of HIV-negative women who smoke are a consequence of cellular recruitment or redistribution as part of a normal response against the damaging agents present in inhaled tobacco smoke, as was suggested by Ekberg-Jansson et al [9]. Recently, investigators reported that tobacco smokers have reduced subepithelial bronchial CD4ϩ T-cell density [10]. The redistribution of CD4ϩ cells from bronchial lining to the periphery may be a plausible explanation for the increase in CD4ϩ cells reported in this communication as well as by others [11,12].…”
Section: Discussionmentioning
confidence: 93%
“…A total of 22 HIV negative women were excluded, because CD4 and CD8 cell counts were unavailable in these participants. Subjects in the original cohort contributed a median (range) of 11 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) visits and those in the new cohort contributed 3 (1-4) visits to the analysis. Baseline characteristics of the study participants are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%